YAP regulates periodontal ligament cell differentiation into myofibroblast interacted with RhoA/ROCK pathway. Issue 4 (20th October 2018) - He, Yao; Xu, Hui; Xiang, Zichao; Yu, Hongyou; Xu, Li; Guo, Yongwen; Tian, Ye; Shu, Rui; Yang, Xianrui; Xue, Chaoran; Zhao, Mengyuan; He, Yiruo; et al.
Abstract: During orthodontic tooth movement (OTM), periodontal ligament cells (PDLCs) receive the mechanical stimuli and transform it into myofibroblasts (Mfbs). Indeed, previous studies have demonstrated that mechanical stimuli can promote the expression of Mfb marker α‐smooth muscle actin (α‐SMA) in PDLCs. Transforming growth factor β1 (TGF‐β1), as the target gene of yes‐associated protein (YAP), has been proven to be involved in this process. Here, we sought to assess the role of YAP in Mfbs differentiation from PDLCs. The time‐course expression of YAP and α‐SMA was manifested in OTM model in vivo as well as under tensional stimuli in vitro. Inhibition of RhoA/Rho‐associated kinase (ROCK) pathway using Y27632 significantly reduced tension‐induced Mfb differentiation and YAP expression. Moreover, overexpression of YAP with lentiviral transfection in PDLCs rescued the repression effect of Mfb differentiation induced by Y27632. These data together suggest a crucial role of YAP in regulating tension‐induced Mfb differentiation from PDLC interacted with RhoA/ROCK pathway. Abstract : Inhibition RhoA/Rho‐associated kinase (ROCK) pathway reduced tension‐induced myofibroblast (Mfb) differentiation and yes‐associated protein (YAP) expression, while overexpressed YAP rescued the repression effect caused by Y27632. YAP played a crucial role in regulating tension‐induced Mfb differentiation from periodontal ligament cells interacted with the RhoA/ROCK pathway.